Mitochondrial DNA Haplogroups and Susceptibility to Neuroblastoma. (25th February 2020) - Chang, Xiao; Bakay, Marina; Liu, Yichuan; Glessner, Joseph; Rathi, Komal S; Hou, Cuiping; Qu, Huiqi; Vaksman, Zalman; Nguyen, Kenny; Sleiman, Patrick M A; Diskin, Sharon J; Maris, John M; et al.
Abstract: Background: Neuroblastoma is a childhood malignancy that arises from the developing sympathetic nervous system. Although mitochondrial dysfunctions have been implicated in the pathophysiology of neuroblastoma, the role of mitochondrial DNA (mtDNA) has not been extensively investigated. Methods: A total of 2404 Caucasian children diagnosed with neuroblastoma and 9310 ancestry-matched controls were recruited at the Children's Hospital of Philadelphia. The mtDNA haplogroups were identified from SNP array data of two independent cohorts. We conducted a case-control study to explore potential associations of mtDNA haplogroups with the susceptibility of neuroblastoma. The genetic effect of neuroblastoma was measured by odds ratios (ORs) of mitochondrial haplogroups. All tests were two-sided. Results: Haplogroup K was statistically significantly associated with reduced risk of neuroblastoma in the discovery cohort consisting of 1474 cases and 5699 controls (OR = 0.72, 95% confidence interval [CI] = 0.57 to 0.90; P = 4.8 × 10 -3 ). The association was replicated in an independent cohort (OR = 0.69, 95% CI = 0.53 to 0.92; P = .01) of 930 cases and 3611 controls. Pooled analysis was performed by combining the two data sets. The association remained highly statistically significant after correction for multiple testing (OR = 0.71, 95% CI = 0.59 to 0.84, P = 1.96 × 10 -4, P corrected = .002). Further analysis focusing on neuroblastoma subtypes indicated haplogroup K was more associated with high-risk neuroblastoma (OR = 0.57, 95% CI = 0.43 to 0.76; P = 1.46 × 10 –4 ) than low-risk and intermediate-risk neuroblastoma. Conclusions: Haplogroup K is an independent genetic factor associated with reduced risk of developing neuroblastoma in European descents. These findings provide new insights into the genetic basis of neuroblastoma, implicating mitochondrial DNA encoded proteins in the etiology of neuroblastoma.